Turismo rural realmente rural - radiografia crítica do turismo no estado de São Paulo - Bovo, Carlos Eduardo Oliveira (2004)
The subject of this work is the agricultural tourism or tourism in agricultural way (agricultural area) and the research has as central concern to identify what it is really this tourist modality. Moreover, it is intended to verify if this modality of tourism can and is assisting in the local development and how this is happening. Thus, we look for to identify the properties and to verify its activities, the services, the equipment and the process of implantation, maintenance and expansion of the modality in the State of São Paulo, through the main existing associations of agricultural tourism and of the referring official agencies to this activity, or either, to mount a data base on this activity in the State of São Paulo in the decade of ninety - time where the activity presented a expressivo growth - being detached the participation of the social citizens and its respective attributions in these enterprises.